The differences of RND between males and females and the correlation between age and RND based on panoramic radiographs - Handayani, Suci; Shantiningsih, Rurie Ratna; Gracea, Rellyca Sola (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Estimating age and sex through several radiographic methods have a significant role in the victim identification process. The mandibular ramus is thought to have a high degree of dimorphism and a close relationship with chronological age, which can be determined by ramus notch depth (RND). This study aimed to analyze the differences in RND between males and females and the correlation between age and RND based on panoramic radiographs. Methods: The type of study is an observational analytic cross-sectional study. The study sample comprised 70 radiographs (35 males and 35 females) aged 19-60 years with complete mandibular permanent dentition, including third molars. The samples were obtained from the database of the Dentomaxillofacial Radiology Installation of RSGM UGM Prof. Soedomo. Analysis of the radiograph was carried out by measuring the RND using EzDent-I Vatech Software with a scale of ratio 1:1. Results: The mean RND value was 2.31 ± 7.95 mm and 1.94 ± 4.93 mm in the male and female groups, respectively. Independent T-test results showed a significant difference (p < 0.05) in RND between the male and female groups. Pearson’s correlation test result did not find any correlation between age and RND in the male dan female group (p > 0.05). Conclusion: RND in males is higher than in females, and there is no correlation between age and RND in both sex groups.Keywords: MISS; trauma of mandible; half face helmet; traffic accidents